RAISING TEACHER’S GRAMMATICAL CONSCIOUSNESS ON ENGLISH MEDIO-PASSIVE CONSTRUCTIONS - Havid Ardi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
Some researchers reported that the EFL learners’ ability in understanding and using tense, aspects, and voice of English at the English Department of Universitas Negeri Padang was not academically satisfied yet. Most EFL learners of English Education department were not in “expected” ability in understanding and using appropriate grammatical constructions both in writing and speaking. This condition may give negative ef-fects to the success of EFL learning in Indonesia. It seems that learners’ and teachers’ grammatical con-sciousness on EFL should be academically and practically raised in such a way that they may have basic and better competency standards. One of stylistic clause constructions in English which is called medio-passive has not yet a well-known construction for many teachers and learners of English in Indonesia. This paper briefly discusses how authentic materials may psychologically and academically raise the grammatical con-sciousness on the medio-passive constructions as part competency standards in EFL. Keywords: medio-passive, grammatical consciousness, authentic materials, competency standards